Acrodermatitis Enteropathica: A Case Report. Issue 20 (May 2016) - Nistor, Nicolai; Ciontu, Lavinia; Frasinariu, Otilia-Elena; Lupu, Vasile Valeriu; Ignat, Ancuta; Streanga, Violeta
Abstract : Abstract: Acrodermatitis enteropathica is a rare genetic autosomal recessive disorder, characterized by periorificial dermatitis, alopecia, and diarrhea. It is caused by mutations in the gene that encodes a membrane protein that binds zinc. We report a 14-month-old boy, admitted for erythematous, scaly and pustular lesions, initially located in the inguinal and perianal regions and on thighs, and very few erythematous lesions on the face. Due to the numerous bacterial skin superinfections with Staphylococcus aureus, including abscesses that required surgical incision, the clinical picture was modified, leading to a delayed establishment of the diagnosis. Later, the symptoms became suggestive for this disease, the diagnostic having been confirmed by low plasma zinc values. Under zinc therapy, skin lesions improved significantly in a few days, with favorable outcome. Two months later, the skin lesions almost disappeared. Abscesses due to bacterial skin superinfections may lead to initially misdiagnosed acrodermatitis enteropathica.